2017
DOI: 10.1128/jcm.02408-16
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of MicroRNA Expression Profiles and Identification of Potential Biomarkers in Leprosy

Abstract: Leprosy is an important cause of disability in the developing world. Early diagnosis is essential to allow for cure and to interrupt transmission of this infection. MicroRNAs (miRNAs) are important factors for host-pathogen interaction and they have been identified as biomarkers for various infectious diseases. The expression profile of 377 microRNAs were analyzed by TaqMan low-density array (TLDA) in skin lesions of tuberculoid and lepromatous leprosy patients as well as skin specimens from healthy controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…al. used single TaqMan assays to validate their findings from a TLDA-analysis, and found that the two methods were reproducible and comparable for 7 of the 16 microRNAs analyzed, and in agreement with our study they could not reproduce the TLDA findings for miR-92a in the qPCR analysis [ 24 ]. Other studies also found, that differences in microRNA levels between groups as detected by TLDA analyses, can only partly be reproduced in a validation cohort by the use of single TaqMan assays [ 25 27 ].…”
Section: Discussionsupporting
confidence: 65%
“…al. used single TaqMan assays to validate their findings from a TLDA-analysis, and found that the two methods were reproducible and comparable for 7 of the 16 microRNAs analyzed, and in agreement with our study they could not reproduce the TLDA findings for miR-92a in the qPCR analysis [ 24 ]. Other studies also found, that differences in microRNA levels between groups as detected by TLDA analyses, can only partly be reproduced in a validation cohort by the use of single TaqMan assays [ 25 27 ].…”
Section: Discussionsupporting
confidence: 65%
“…26 The widespread overexpression of miR-27a in cancer has led to the belief that miR-27a is an oncogenic miRNA. 27 In the present study, miR-27a was upregulated in patients with metastases, suggesting that its upregulation was acquired in the course of tumor progression and during the acquisition of metastatic potential. Several studies have revealed the prognostic significance of miR-27a overexpression in various carcinomas, such as gastric cancer, 28 acute lymphoblastic leukemia, 29 and osteosarcoma.…”
Section: Discussionsupporting
confidence: 52%
“…Both the univariate analyses and multivariate ana-lyses indicated that miR-27a expression was an independent prognostic factor for BC progression. 27 Anti-apoptosis functions of miR-29a in BC cells have been reported by Choghaei et al 32 These controversial results of miR-29a in tumors indicated that based on the cancer type, miR-29a played different roles. In our study, we found that miR-29a was significantly upregulated in BC as compared with normal tissues, indicating that miR-29a was implicated in the progression of BC.…”
Section: Discussionmentioning
confidence: 93%
“…Due to their presence in the bodily fluids, exosomes are considered candidate biomarkers. The use of a combination of miRNAs as biomarkers, instead of one unique miRNA, has been considered to be a more powerful tool due to the possible overlap in miRNA targeting [ 49 ]. A miRNA may dampen or amplify a signal by participating in a negative or positive feedback loop [ 50 ].…”
Section: Discussionmentioning
confidence: 99%